Religião e individuação: fenomenologia do desenvolvimento humano através da direção espiritual - Santos, Elismar Alves dos (2006)
The current work, theorical-empirical, about the subjective power of spiritual direction attemps to rescue the humanizing psychological dimension of this old and actual Catholic-Cristian religious practice. The techinique used to explore the humanizer meanings experienced by the four searched subjects, is qualitative with phenomenological background. The results point to the efficacy of this religious practice en the fiel of the human adjustment and development, as well as stress its effects to the experience of a religiosity that is more solid and human.